Sex-specific outcomes in cancer therapy: the central role of hormones - Bakhshi, Parisa; Ho, Jim Q.; Zanganeh, Steven (Frontiers in Medical Technology, 2024)
Sex hormones play a pivotal role in modulating various physiological processes, with emerging evidence underscoring their influence on cancer progression and treatment outcomes. This review delves into the intricate relationship between sex hormones and cancer, elucidating the underlying biological mechanisms and their clinical implications. We explore the multifaceted roles of estrogen, androgens, and progesterone, highlighting their respective influence on specific cancers such as breast, ovarian, endometrial, and prostate. Special attention is given to estrogen receptor-positive (ER+) and estrogen receptor-negative (ER−) tumors, androgen receptor signaling, and the dual role of progesterone in both promoting and inhibiting cancer progression. Clinical observations reveal varied treatment responses contingent upon hormonal levels, with certain therapies like tamoxifen, aromatase inhibitors, and anti-androgens demonstrating notable success. However, disparities in treatment outcomes between males and females in hormone-sensitive cancers necessitate further exploration. Therapeutically, the utilization of hormone replacement therapy (HRT) during cancer treatments presents both potential risks and benefits. The promise of personalized therapies, tailored to an individual’s hormonal profile, offers a novel approach to optimizing therapeutic outcomes. Concurrently, the burgeoning exploration of new drugs and interventions targeting hormonal pathways heralds a future of more effective and precise treatments for hormone-sensitive cancers. This review underscores the pressing need for a deeper understanding of sex hormones in cancer therapy and the ensuing implications for future therapeutic innovations.